Penatalaksanaan Selulitis Periorbital Akibat Abses Gigi pada Anak - Kusuma Wardhani, Febriyanti (Bhakta Dental Journal, 2024)
Orbital cellulitis is a rare but serious complication of dental infection and if left untreated can progress to blindness, cavernous sinus thrombosis, meningitis, subdural empyema, brain abscess and death. Awareness of the possible spread of odontogenic infection to the eye socket is important, so that appropriate treatment can be initiated as early as possible. The case of a three-year-old five-month-old girl presented with a three-day history of progressive right periorbital swelling associated with low-grade fever. The swelling first appeared in the right upper perioral region, extending upward to the right cheek and right lower eyelid. However, no red eye was observed, nor were there any watery, eye, ear, or nasal discharge. There is no history of trauma. Intraoral examination of the upper right area revealed 52 residual root elements, 53 irreversible pulpitis and 54 pulp necrosis with the upper pulp uncovered. Oral hygiene was poor in the area of tooth 54 where the mucobuccal folds were found to be raised and reddish, making tooth 54 the suspect cause of odontogenic infection. The therapy given was removal of the pulp roof on tooth 54 and medication in the form of D5 fluid infusion, intravenous injection of ceftriaxone, santalgesic, ranitidine and dexamethasone. There was significant improvement after 3 days of treatment. Periorbital cellulitis in this case is an odontogenic case that can be fatal if not treated properly. this case shows how important the treatment of pediatric primary teeth is.